DETERMINATION OF BIOACTIVE COMPONENTS OF ANNONA SQUAMOSA L LEAF BY GC- MS ANALYSIS (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Annona squamosa Linn, commonly known as Sugar apple, belonging to the family Annonaceae, is said to show varied medicinal effects, including insecticide, antiovulatory and abortifacient. Hence the present investigation was carried out to determine the chemical composition of Annona squamosa leaf extract using Gas Chromatography–Mass Spectrometry technique, while the mass spectra of the compounds found in the extract was matched with the National Institute of Standards and Technology (NIST) library. GC-MS analysis of Annona squamosa leaf extract revealed the existence of Sodium benzoate (27.50%), 4, 4-Tert- Butylcalix(4)arene (12.34 %), 4, 4- Dimethylcholesterol (10.30%), Butyloctylpthalate (9.67%), stigmasterol acetate (2.92%), isoamylacetyate (2.29%) justifying the use of this plant to treat many ailments in folk and herbal medicine.